The potential role of GLP-1 receptor agonists in substance use disorders – a systematic review - Völker, K. M.; Prechtl, B. L. H.; Bormann, N. L.; Choi, D. S. (Frontiers in Pharmacology, 2026)
BackgroundSubstance use disorders (SUDs) remain a major global health challenge with limited pharmacological treatment options and high relapse rates. Glucagon-like peptide-1 receptor agonists (GLP-1RAs), originally developed for type 2 diabetes and obesity, have recently gained attention for their potential effects on addictive behaviors. Preclinical and early clinical studies suggest that GLP-1RAs modulate mesolimbic dopaminergic signaling and attenuate reward-driven behaviors, positioning them as promising candidates for novel interventions in addiction medicine.MethodsWe conducted a systematic literature review in accordance with PRISMA 2020 guidelines, with protocol registration in PROSPERO (CRD42024571356). Searches were performed across PubMed, Embase, Web of Science, PsycINFO, and the Cochrane Library up to January 2025. Eligible studies included preclinical and clinical investigations examining GLP-1RAs in alcohol, nicotine, cocaine, and opioid use disorders. Data were extracted on study design, sample characteristics, interventions, and primary outcomes related to substance use behavior and neurobiological mechanisms.ResultsA total of 41 studies were included, comprising 35 preclinical and six clinical investigations. Preclinical evidence consistently demonstrated that GLP-1RAs, including exendin-4, liraglutide, and semaglutide, reduced substance intake, relapse-like behaviors, and cue-induced drug seeking across multiple drug classes. These effects were linked to GLP-1R activation in brain reward circuits, including the nucleus accumbens, ventral tegmental area, and nucleus of the solitary tract. Clinical studies provided preliminary support, particularly for alcohol use disorder, with GLP-1RAs showing reductions in alcohol consumption and craving in several clinical trials. However, clinical findings remain heterogeneous and limited by small sample sizes and short study durations.ConclusionThis systematic review highlights GLP-1RAs as a promising therapeutic approach for SUDs, targeting the neurobiological pathways underlying both metabolic and reward regulation. While preclinical data are convincing, clinical evidence remains preliminary, underscoring the need for larger, well-designed randomized controlled trials. GLP-1RAs may represent a novel pharmacological strategy bridging metabolic and neuropsychiatric domains in addiction treatment.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024571356.